Bench‐to‐bedside: Bridge‐enhanced anterior cruciate ligament repair. Issue 12 (9th July 2017) - Perrone, Gabriel S.; Proffen, Benedikt L.; Kiapour, Ata M.; Sieker, Jakob T.; Fleming, Braden C.; Murray, Martha M.
ABSTRACT: Anterior cruciate ligament (ACL) injuries are one of the most well‐known orthopaedic injuries and are treated with one of the most common orthopaedic procedures performed in the United States. This surgical procedure, ACL reconstruction, is successful at restoring the gross stability of the knee. However, the outcomes of ACL reconstruction can be limited by short and long‐term complications, including muscle weakness, graft rupture, and premature osteoarthritis. Thus, new methods of treating this injury are being explored. This review details the pathway of how a tissue engineering strategy can be used to improve the healing of the ACL in preclinical studies and then translated to patients in an FDA‐approved clinical study. This review paper will outline the clinical importance of ACL injuries, history of primary repair, the pathology behind failure of the ACL to heal, pre‐clinical studies, the FDA approval process for a high risk medical device, and the preliminary results from a first‐in‐human study. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2606–2612, 2017.